Use and Effectiveness of Intraperitoneal Chemotherapy for Treatment of Ovarian Cancer. Issue 11 (November 2015) - Wright, Alexi A.; Cronin, Angel; Milne, Dana E.; Bookman, Michael A.; Burger, Robert A.; Cohn, David E.; Cristea, Mihaela C.; Griggs, Jennifer J.; Keating, Nancy L.; Levenback, Charles F.; Mantia-Smaldone, Gina; Matulonis, Ursula A.; et al.
Abstract : ABSTRACT: This prospective cohort study tested the hypothesis that use of intraperitoneal/intravenous (IP/IV) chemotherapy in clinical practice would be associated with improved survival compared with IV chemotherapy, despite frequent modifications to the GOG protocol 172 (GOG-172) regimen. The use and effectiveness of IP/IV chemotherapy were examined in 823 patients who received a diagnosis of stage III, optimally cytoreduced ovarian cancer diagnosed at 6 National Comprehensive Cancer Network centers between 2003 and 2012. The association between use of IP/IV chemotherapy with overall survival and with treatment-related toxicities was assessed with Cox regression and logistic regression, respectively, in a propensity score–matched sample of 402 patients diagnosed from 2006 to 2012. Trial participants were excluded to minimize selection bias. The use of IP/IV chemotherapy increased between 2003 and 2006 from 0% to 33% and increased from 2007 to 2008 by nearly 50% but plateaued thereafter. Between 2006 and 2012, there was a significant variation among the 6 centers in adoption of IP/IV chemotherapy ( P < 0.001; unadjusted range, 4%–67%). At initiation of treatment, 43% of patients received modified IP/IV regimens. Compared with IV chemotherapy, IP/IV chemotherapy had a significantly improved overall survival (3-year overall survival, 81% vs 71%; hazard ratio, 0.68; 95% confidence interval, 0.47–0.99; P < 0.05), but was associated with a greater likelihood of change in treatments as a result of treatment-related toxicities (adjusted rates of discontinuation or change [20.4% vs 10.0%; adjusted odds ratio, 2.83; 95% confidence interval, 1.47–5.47; P < 0.002]). The data show a clear survival benefit for IP/IV chemotherapy over IV treatment outside a clinical trial among women with optimally debulked, stage III ovarian cancer. Although use of IP/IV chemotherapy at the 6 cancer centers increased significantly between 2003 and 2012, less than 50% of eligible patients received it. Increased use of IP/IV chemotherapy use in clinical practice appears to be an important and underused strategy to improve ovarian cancer outcomes.